PENGARUH KOMPONEN ARUS KAS DAN INFORMASI LABA TERHADAP RETURN SAHAM - Cindy Zuristiana Dwi Sastia; Suwandi Suwandi (PROCEEDING UMSURABAYA, 2022)
This study aims to examine the effect of cash flow components and earnings information on stock returns. The population used is LQ45 companies listed on the IDX in 2017-2019. The sample of this research is 120 samples selected based on purposive sampling technique. This study uses quantitative methods with secondary data sources in the form of complete company annual financial reports. The data analysis technique used multiple linear regression analysis. The results showed that the variables of accounting profit and operating cash flow had no effect on stock returns. Meanwhile, the variables of investment cash flow and financing cash flow have a significant effect on stock returns.Keywords:Accounting Profits; Operating Cash Flow; Investment Cash Flow; Funding Cash Flow; Stock ReturnÂ